Usage of Knowledge Innovation Repository of Agriculture in the North East (KIRAN) services by the farmers of Meghalaya - Sumi, Ditolyn; Kharmudai, Achin; P, Jyothi S.S. (Indian Journal of Hill Farming, 2018)
ICT tools have become closely intertwined with the lives of the people, as it makes communication easier, faster and cheaper for its users. Knowledge Innovation Repository of Agriculture in North East (KIRAN) is an information portal for agriculture started in the year 2012 by ICAR Research Complex for North-East Region. The focus of the study was on the usage of KIRAN services by the farmers. The study was conducted among the registered farmers of KIRAN in Ri Bhoi district of Meghalaya and it was found that information provided on general aspects in agriculture were used by majority of the farmers (71.70%) with a frequency of sometimes only (61.70%), while other information on alerts, market, finance and trainings were not used by the majority. All kinds of information provided through KIRAN were perceived as useful while information most required was given to market information followed by the information on financial support. Highest priority of perceived benefits of KIRAN was given to minimization of time and distance barriers, followed by the benefit of saving the cost to obtain information as the next priority. Poor socio economic condition of the farmers emerged as the most prominent constraint followed by poor follow-up extension facility.